2012
DOI: 10.1063/1.4719674
|View full text |Cite
|
Sign up to set email alerts
|

Efficient terahertz generation by optical rectification in Si-LiNbO3-air-metal sandwich structure with variable air gap

Abstract: A record high optical-to-terahertz conversion efficiency of 0.25% was realized with femtosecond laser pulses propagated in a planar Si-LiNbO3-air-metal structure. Terahertz spectrum tuning was demonstrated by adjusting an air gap between the LiNbO3 layer and the metal plate. The influence of optical pulse chirp on the efficiency of terahertz generation was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 19 publications
1
31
0
Order By: Relevance
“…However, the large index dispersion and mismatch in LiNbO3 inhibit efficient phase matching in a collinear geometry. Since Hebling et al suggested a non-collinear phase matching in a prism-cut LiNbO3 using a tilted pulse-front pumping (TPFP) scheme and reported its proof-of-principle experiment for efficient THz pulse generation in 2003, many efforts have followed to improve both THz pulse energy and spectral bandwidth by utilizing different configurations and excitation sources [15][16][17]. As a result, it turned out that there was a tradeoff between the pump-to-THz conversion efficiency and the spectral bandwidth for THz pulse generation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the large index dispersion and mismatch in LiNbO3 inhibit efficient phase matching in a collinear geometry. Since Hebling et al suggested a non-collinear phase matching in a prism-cut LiNbO3 using a tilted pulse-front pumping (TPFP) scheme and reported its proof-of-principle experiment for efficient THz pulse generation in 2003, many efforts have followed to improve both THz pulse energy and spectral bandwidth by utilizing different configurations and excitation sources [15][16][17]. As a result, it turned out that there was a tradeoff between the pump-to-THz conversion efficiency and the spectral bandwidth for THz pulse generation.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] In case of materials with high nonlinearity but strong absorption in the THz range, such as LiNbO 3 (LN) with d 33 ¼ 168 pm/V nonlinear optical coefficient 10 and tens of cm À1 absorption coefficient, 11 it is important to suppress absorption. A promising way to achieve this is to sandwich a few lm thick LN layer between layers of significantly smaller absorption.…”
mentioning
confidence: 99%
“…A promising way to achieve this is to sandwich a few lm thick LN layer between layers of significantly smaller absorption. [1][2][3][4][5] A suitable material for such a lowabsorption cladding is silicon (Si). The structures reported so far are guiding only the optical pump; 1-5 the selected material parameters and dimensions do not allow wave guiding in the THz range.…”
mentioning
confidence: 99%
“…We propose using this phenomenon to improve the spectral characteristics of one of the most efficient optical-to-terahertz converters: a thin LiNbO 3 layer attached to a Si-prism outcoupler.One of the most efficient optical-to-terahertz converters is the structure consisting of a thin (∼30 − 50 μm thick) layer of LiNbO 3 (LN) attached to a Si-prism outcoupler [1][2][3][4][5]. A femtosecond laser pulse propagates in the LN layer as a guided mode and produces (via optical rectification) nonlinear polarization, which follows the optical intensity envelope.…”
mentioning
confidence: 99%